Islamic Religious Education Using Technology for Discourse - Salsabila, Unik Hanifah (Proceeding International Conference on Religion, Science and Education, 2022)
Philosophy's function in multidisciplinary integration is critical for systematics and framework development. The study's findings may aid in developing the following fields, both theoretically and practically, most notably Islamic Religious Education. This research aims to ascertain the direction of multidisciplinary studies in Islamic Religious Education by analyzing educational technology perspectives from two influential figures: Noeng Muhadjir from the field of Islamic educational philosophy and Yusuf Hadi Miarso from the field of educational technology. This research entails a literature review, a content analysis, a qualitative analysis, and a descriptive narrative analysis. The key sources for thought studies are Noeng Muhadjir's qualitative research books (Positivistic, Rationalistic, Phenomenological, and Metaphysic Realism in the Study of Texts and Religious Research) Yusuf Hadi Miarso's book Sowing the Seeds of Educational Technology. Noeng Muhadjir characterizes the evolution of Islamic religious education as a normative discipline containing the conditions of science philosophy that scholars in their domains must meet. By contrast, Yusuf Hadi Miarso's perspective embraces the field and scope of educational technology development as an integrative subject of research. Who in Indonesia has witnessed irreversible changes in the context of disciplines? The research results from a new discourse viewpoint on building transdisciplinary Islamic religious education research using an educational technology lens. This research permits the systematic development of multidisciplinary Islamic religious education by addressing the following discipline- and technological-specific needs. The findings of this literature study are used to compensate for misunderstandings and biases regarding the present era's utilization of the multidisciplinary Islamic Religious Education research model. The development of multidisciplinary Islamic education from a technological viewpoint is necessary for the arena of practice to contribute to applicable and normative science by incorporating philosophical and technological elements simultaneously.